PA 14-3-2098 Implementation of a risk prediction model into drowning prevention policy: a scoping review. (November 2018) - Tellier, Eric; Salmi, Louis-Rachid; Simonnet, Bruno
Abstract : Background: Along beaches of Gironde, in South-Western France, 573 drowning occurred from 2011 to 2016, leading to 24 deaths. Rip currents are known as a major cause of drownings in this area. Following the development and test of a model able to forecast drowning risk up to three days, we wanted to identify issues to be considered to use prediction models in drowning prevention strategies. The objective of our scoping review was to map the existing literature and to identify what outcomes where measured by the current research on both drowning prevention and prediction models. Methods: We included all quantitative and qualitative research designs. An initial limited search on Medline and Google Scholar was undertaken, followed by an analysis of keywords and abstracts. A second search using all identified keywords was then undertaken. Results: In the 886 articles identified initially, we found one predictive model of rip currents and one model of real-time risk assessment. None were integrated into any intervention study. The second search led to 190 articles. After discarding 147 articles based on title or abstract, we found 6 articles studying risk-related behavior in other fields (aviation and avalanche), 6 discussing behavioral theories into injury prevention; 7 others analyzed beachgoers beliefs and behavior, 7 were intervention studies, and 2 analyzed lifeguards' decisions. Finally, six reviews about drowning prevention were read. Conclusion: As drowning prevention implies risk awareness and a behavior change from beachgoers, we are developing an intervention based on behavioral theories and following a standard behavior change design. The impact of this intervention integrating a risk prediction model, able to consider time-fluctuation of the numbers of drowning events, will be assessed by an experimental or quasi-experimental design.